Penggunaan Modul Berbasis SETS dalam Pembelajaran Biologi - Yendrita Yendrita (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2020)
This study aims to determine the effect of the use of SETS-based modules in learning biology in Class X Man 1 Payakumbuh students. This type of research is a quasi-experimental study. The research instrument is a set of questions. Samples were taken by random sampling technique, the subjects of this study were all students of class X majoring in MIA MAN 1 Payakumbuh who were enrolled in the academic year 2017/2018 consisting of 2 classes. Data were analyzed by t test. The results showed that the learning outcomes of biology in class with SETS-based modules were significantly higher, where the average learning outcomes in the module class was 78.95, while the average learning outcomes in conventional classes was 69.47. T test results obtained th = 3.42 and tt = 1.68 (for α = 0.05) and tt = 2.42 (for α = 0.01). Means the hypothesis is accepted at 95% and 99% confidence level. Conclusion, biology learning outcomes in class using SETS-based modules are higher than class learning outcomes with conventional learning in class X MAN 1 Payakumbuh. Keywords: Learning Outcomes, Biology Learning, SETS-based Modules